Religious Nationalism in an Age of Globalization: The Case of Paraguay's "Mennonite State" (Almanack, 2021)
This article uses the example of Mennonite nation-building in Paraguay during the 1920s and 1930s to argue that state formation is not inherently modernist. Tracing nineteenth and early twentieth-century discourses of Mennonite colonies in Imperial Russia, Canada and elsewhere as a state "within a state", the essay advocates a reevaluation of theories of modern statehood advanced by thinkers like James C. Scott and Ernest Gellner. As conservative, pacifist Mennonites traveled from North America to the Paraguayan Chaco to escape the pressures of assimilation in democratic society, their migration paved the way for coreligionists fleeing persecution in the Soviet Union to join in a formation of a rural, autonomus "Mennonite state" that was organized internationally, characterized by deep religious observance, and conceived in opposition to high modernist projects.